Perspectives on Teacher Education and Development (University of Maribor Press, 2023)
The scientific monograph entitled "Perspectives on teacher education and development" is the work of authors from different professional and scientific backgrounds, coming from a broader international area. The publication consists of 38 original scientific contributions addressing different aspects of teacher education and training and highlighting some of the major challenges in this field. Particular aspects such as contemporary didactic and pedagogical approaches, digital transformation of education, inclusiveness, educational policies, curricula, leadership, and personal and professional development of teachers are highlighted. The monograph highlights some of the important issues that can also be reflected in changes at the systemic level.